Sudan Programmatic Poverty Assessment : Poverty and Inequality in Sudan, 2009-2014 - World Bank (World Bank, Washington, DC, 2020)
Sudan is at a critical juncture regarding the direction of its economy and its development path. The loss of a large share of oil revenues in the wake of the secession of South Sudan has given rise to a period of growing macroeconomic imbalances and moderately low rates of economic growth. Despite periodic adjustment measures, inadequate policies, including deficit monetization, have exacerbated macroeconomic imbalances. This report on poverty and shared prosperity in Sudan, covering 2009 to 2014 is structured as follows: Chapter II provides background information on sociodemographic characteristics of Sudan’s population, Sudan’s political developments, as well as recent macroeconomic trends; Chapter III provides a profile of monetary poverty and inequality with a focus on trends and drives over 2009–2014; Chapter IV provides a non-monetary poverty profile that covers demographics, education, access to productive assets, ownership of durable consumption goods, housing conditions and rent, and access to services; To rationalize the observed trends in poverty and inequality, Chapter V explores trends in labor markets, including labor productivity, labor market participation, employment, wages, and returns to education; Chapter VI provides an analysis of shocks, coping strategies, and transfers, including international remittances; and the final chapter summarizes and provides policy implications.